The role of the annexin A protein family at the maternal–fetal interface - Hu, Jingwen; Chen, Lin; Ruan, Jing; Chen, Xiaoyan (Frontiers in Endocrinology, 2024)
Successful pregnancy requires the tolerance of the maternal immune system for the semi-allogeneic embryo, as well as a synchrony between the receptive endometrium and the competent embryo. The annexin family belongs to calcium-regulated phospholipid-binding protein, which functions as a membrane skeleton to stabilize the lipid bilayer and participate in various biological processes in humans. There is an abundance of the annexin family at the maternal–fetal interface, and it exerts a crucial role in embryo implantation and the subsequent development of the placenta. Altered expression of the annexin family and dysfunction of annexin proteins or polymorphisms of the ANXA gene are involved in a range of pregnancy complications. In this review, we summarize the current knowledge of the annexin A protein family at the maternal–fetal interface and its association with female reproductive disorders, suggesting the use of ANXA as the potential therapeutic target in the clinical diagnosis and treatment of pregnancy complications.